2015
DOI: 10.1259/dmfr.20150041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effective dose of cone beam CT and multislice CT for temporomandibular joint examinations at optimized exposure levels

Abstract: Objectives: To compare the effective dose to patients from temporomandibular joint examinations using a dental CBCT device and a multislice CT (MSCT) device, both before and after dose optimization. Methods: A Promax ® 3D (Planmeca, Helsinki, Finland) dental CBCT and a LightSpeed VCT ® (GE Healthcare, Little Chalfont, UK) multislice CT were used. Organ doses and effective doses were estimated from thermoluminescent dosemeters at 61 positions inside an anthropomorphic phantom at the exposure settings in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…In the tomographic axial plane rotational condylar movements are observed after surgery despite of condylar transoperative repositioning, most condylar position studies have omitted this measurement and have measured the condyle bi-dimensionally only. Also in the axial tomographic plane lateromedial condylar movements and "sag" can be observed, but have been negligible during postoperative clinical examination [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the tomographic axial plane rotational condylar movements are observed after surgery despite of condylar transoperative repositioning, most condylar position studies have omitted this measurement and have measured the condyle bi-dimensionally only. Also in the axial tomographic plane lateromedial condylar movements and "sag" can be observed, but have been negligible during postoperative clinical examination [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…Some exhibit significantly lower patient doses than conventional CT. 10,18,19 This might be a result of optimization of CT protocols in the last few years as one study found that dependent on the model, radiation in multislice CT could be reduced after protocol optimization below radiation dose in cone-beam CT. 20 Another study found that cone-beam CT yielded significantly higher effective doses than CT but it could be reduced to equal and lower than CT after optimization. 21 The scan time varies between 20 and 24 s. This is likely to influence image quality in clinical application, especially for imaging close to the trunk, where breathing and heart movement will cause movement artifacts. Particularly, imaging in the upright position in elderly and patients with pain will be prone to movement artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Often, its diagnostic accuracy and reliability are better than that of two‐dimensional (2D) images 1 . CBCT provides comparable diagnostic accuracy with a relatively lower radiation dose and cost compared with medical computed tomography (CT) 2‐4 and, at present, is considered the technique of choice for evaluating osseous changes of the TMJ 5 …”
Section: Introductionmentioning
confidence: 99%